Ischemic optic neuropathy following craniotomy - Chaudhary, Ranjit Kumar; Chaudhary, Sanjib Kumar; Gupta, Elina; Raghuram, Karthikram (Journal of Nepal Health Research Council, 2023)
Ischemic optic neuropathy is one of the major causes of severe impairment of vision often leading to blindness. It has varied etiopathogenesis with limited management options and very often result in poor outcome. Perioperative ischemic optic neuropathy is rare and particularly seen in elderly patients with multiple comorbidities undergoing cardiac or spine surgery. We present a case of young patient who developed ischemic optic neuropathy following craniotomy for recurrent meningioma. Keywords: Ischemic optic neuropathy; optic nerve vasculature; painless vision loss; perioperative complications; perioperative optic nerve ischemia